2006
DOI: 10.1080/03008200600995940
|View full text |Cite
|
Sign up to set email alerts
|

Bouts of Passive Stretching after Immobilization of the Rat Soleus Muscle Increase Collagen Macromolecular Organization and Muscle Fiber Area

Abstract: This study evaluated the effect of short bouts of stretching on the soleus muscle after immobilization, by measuring the birefringence of the intramuscular connective tissue (ICT) and the muscle fiber area. Thirty rats were divided into five groups: the left soleus was immobilized in the shortened position; after immobilization the animals remained free; after immobilization, the soleus was stretched daily (10 stretches of 60 sec followed by 30 sec rest); after immobilization, the soleus was stretched 3 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 51 publications
2
43
0
11
Order By: Relevance
“…The data of this study showed that in a 3 times a week frequency, the stretching protocol applied isolated in the intact muscle was sufficient to prevent connective tissue proliferation compared to muscles injured and submitted to laser and stretching, corroborated with Coutinho et al 33 Endorsing the effect of the stretching protocol applied in the intact muscles (SG), we found an increase in the serial sarcomere number compared to control group (CG). Other authors observed an addition in the serial sarcomere number of intact soleus muscle, applied 3 times a week, however, it was maintained for 40 min 27 .…”
Section: Discussionsupporting
confidence: 89%
“…The data of this study showed that in a 3 times a week frequency, the stretching protocol applied isolated in the intact muscle was sufficient to prevent connective tissue proliferation compared to muscles injured and submitted to laser and stretching, corroborated with Coutinho et al 33 Endorsing the effect of the stretching protocol applied in the intact muscles (SG), we found an increase in the serial sarcomere number compared to control group (CG). Other authors observed an addition in the serial sarcomere number of intact soleus muscle, applied 3 times a week, however, it was maintained for 40 min 27 .…”
Section: Discussionsupporting
confidence: 89%
“…The use of stretching to prevent and treat contractures after immobilization is supported by numerous animal studies [3,8,12,30,32,39,40]. Ample evidence from these animal studies suggests that contracture management can be achieved through repeated or sustained stretching in the case of contractures not attributable to injury to the central nervous system [3,8,10,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Não há aumento de fl exibilidade quando a duração do alongamento é aumentada de 30 a 60 segundos, ou quando a frequência de alongamento é aumentada de uma a três vezes por dia (18,23). Corroborando com outros estudos (13,14,18,22,23), optou-se pela realização de apenas uma única sessão de alongamento estático e sua sustentação por um período de 60 segundos, sendo observada sua efi cácia nos alongamentos.…”
Section: Discussionunclassified
“…Os exercícios de alongamento aumentam a extensibilidade dos tecidos moles e restauram o comprimento muscular por afetar as propriedades contráteis da fi bra muscular e pelas alterações viscoelásticas promovidas na unidade músculo-tendão (10)(11)(12)(13)(14)(15)(16)(17). O alongamento produz efeitos imediatos e uma única sessão em indivíduos saudáveis é capaz de melhorar a fl exibilidade muscular (amplitude máxima passiva fi siológica) e a mobilidade articular (10).…”
unclassified
See 1 more Smart Citation